Mathematical modelling of rod photoreceptor metabolism - Kunpasuruang, Wannapa (2009)
Rod photoreceptors are cells that sense and receive light. They consist of two major parts, an outer and an inner segment, which are linked by a connecting cilium. Continual growth of the rod outer segment is balanced by shedding of the tip of the outer segment. We start this thesis by developing nonlinear ordinary differential equations to describe the metabolic activity of the rod photoreceptor cells in order to investigate whether changes in metabolic demand during periods of light and dark are responsible for the observed (daily) variation in the length of the outer segment of the rod photoreceptors. Analysis of the rod system is carried out by investigating the steady-state solutions.